Naturalistic reading of multi-page texts elicits spatially extended modulation of oscillatory activity in the right hemisphere - Sasu Mäkelä; Jan Kujala; Pauliina Ojala; Jukka Hyönä; Riitta Salmelin (Scientific Reports)
Abstract The study of the cortical basis of reading has greatly benefited from the use of naturalistic paradigms that permit eye movements. However, due to the short stimulus lengths used in most naturalistic reading studies, it remains unclear how reading of texts comprising more than isolated sentences modulates cortical processing. To address this question, we used magnetoencephalography to study the spatiospectral distribution of oscillatory activity during naturalistic reading of multi-page texts. In contrast to previous results, we found abundant activity in the right hemisphere in several frequency bands, whereas reading-related modulation of neural activity in the left hemisphere was quite limited. Our results show that the role of the right hemisphere may be importantly emphasized as the reading process extends beyond single sentences.